Effect of the CXCR4 antagonist plerixafor on endogenous neutrophil dynamics in the bone marrow, lung and spleen. Issue 6 (6th May 2020) - Pillay, Janesh; Tregay, Nicola; Juzenaite, Goda; Carlin, Leo M.; Pirillo, Chiara; Gaboriau, David C. A.; Farahi, Neda; Summers, Charlotte; Lo Celso, Cristina; Chilvers, Edwin R.; Rankin, Sara; De Filippo, Katia
Abstract: Treatment with the CXCR4 antagonist, plerixafor (AMD3100), has been proposed for clinical use in patients with WHIM (warts, hypogammaglobulinemia, infections, and myelokathexis) syndrome and in pulmonary fibrosis. However, there is controversy with respect to the impact of plerixafor on neutrophil dynamics in the lung, which may affect its safety profile. In this study, we investigated the kinetics of endogenous neutrophils by direct imaging, using confocal intravital microscopy in mouse bone marrow, spleen, and lungs. Neutrophils are observed increasing their velocity and exiting the bone marrow following plerixafor administration, with a concomitant increase in neutrophil numbers in the blood and spleen, while the marginated pool of neutrophils in the lung microvasculature remained unchanged in terms of numbers and cell velocity. Use of autologous radiolabeled neutrophils and SPECT/CT imaging in healthy volunteers showed that plerixafor did not affect GM-CSF-primed neutrophil entrapment or release in the lungs. Taken together, these data suggest that plerixafor causes neutrophil mobilization from the bone marrow but does not impact on lung marginated neutrophil dynamics and thus is unlikely to compromise respiratory host defense both in humans and mice.